Electrochemical devices and electronic devices
By setting the basecoat layer in the negative electrode sheet of the lithium-ion battery and adjusting the thickness ratio and compaction density of the material layer, the risk of current collector caused by the expansion and contraction of the negative electrode active material layer during the charging and discharging process is solved, and a lower risk of battery deformation and better electrochemical performance is achieved.
Patent Information
- Application Number
- CN202210352599.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-03-31
AI Technical Summary
During the charging and discharging process of lithium-ion batteries, the risk of current collector wrinkles and cracks caused by the expansion and contraction of the negative electrode active material layer, which increases the possibility of battery deformation.
By setting the basecoat layer in the negative electrode sheet and adjusting the thickness ratio and compaction density between the negative electrode active material layer and the current collector, it satisfies a specific relationship (3.8≤100×(S/L)+P≤14), the adhesion and conductivity of the current collector and the active material layer are improved.
It effectively reduces the risk of current collector wrinkles and fracture caused by the expansion and contraction of the negative electrode active material layer, reduces the possibility of battery deformation, and improves the cycling and dynamic performance of the electrochemical device.
Smart Images

Figure BDA0003576381870000131 
Figure BDA0003576381870000141 
Figure BDA0003576381870000151
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices, such as lithium-ion batteries, are widely used in laptop computers, mobile phones, and new energy electric vehicles. This places higher demands on electrochemical devices to maintain low volume expansion while maintaining high energy density. During the charge and discharge process of lithium-ion batteries, the active material layer expands and contracts as lithium ions move, so that the copper foil as the current collector is also subjected to deformation loads during each charge and discharge. The stress generated by the expansion and contraction of the active material is transmitted to the current collector through the base coating. If the copper foil undergoes plastic deformation due to expansion during charging, the copper foil will wrinkle during the next contraction; similarly, if the copper foil undergoes plastic deformation due to contraction during discharge, the copper foil will be at risk of rupture during the next expansion. Summary of the invention
[0003] In view of the problems existing in the background technology, the purpose of the present application is to provide an electrochemical device that can effectively improve the risks of current collector wrinkling, rupture, etc. caused by the expansion and contraction of the negative electrode active material layer, thereby reducing the risk of battery deformation.
[0004] In order to achieve the above-mentioned object, the present application provides an electrochemical device, which includes a negative electrode sheet, wherein:
[0005] The negative electrode sheet comprises a negative electrode current collector, a negative electrode bottom coating layer and a negative electrode active material layer;
[0006] The primer layer is disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer is disposed on the primer layer;
[0007] The thickness S (μm) of the negative electrode undercoat layer, the thickness L (μm) of the single-sided negative electrode active material layer, the compaction density P (g / cm 3 ) satisfy the relationship between:
[0008] 3.8≤100×(S / L)+P≤14.
[0009] In some embodiments, the thickness S (μm) of the negative electrode bottom coating, the thickness L (μm) of the single-sided negative electrode active material layer, and the compaction density P (g / cm 3 ) satisfy the relationship between:
[0010] 4.5≤100×(S / L)+P≤7.5.
[0011] In some embodiments, the ratio of the thickness S (μm) of the negative electrode undercoat layer to the thickness L (μm) of the single-sided negative electrode active material layer is 1:8-1:150.
[0012] In some embodiments, the thickness S of the negative electrode undercoat layer is 1 μm-5 μm.
[0013] In some embodiments, the OI value V OI From 15 to 25.
[0014] In some embodiments, the L value ranges from 40 μm to 100 μm.
[0015] In some embodiments, the P is from 1.1 g / cc to 1.8 g / cc.
[0016] In some embodiments, the electrochemical device further comprises an electrolyte; in some embodiments, the electrolyte comprises a sulfur-oxygen double bond compound; in some embodiments, based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is M (%) and the specific surface area of the negative electrode active material is A (m 2 / g) satisfies: 0.3≤M / A≤3.
[0017] In some embodiments, the sulfur-oxygen double bond compound is selected from at least one of methylene disulfonate, vinyl sulfate, propylene sulfate, 1,3-propane sultone, 1,4-butane sultone, ethylene sultone, 1,3-propene sultone, 1,4-butene sultone, 1-methyl-1,3-propene sultone, divinyl sulfone, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, and methyl vinyl sulfone.
[0018] In some embodiments, the thickness D (μm) of the negative electrode current collector satisfies: 50≤400×(D / L)+V OI ≤100; where V OI Indicates the orientation index of the negative electrode active material, according to V OI =C 004 / C 110 Calculate, C 004 is the peak area of the 004 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode, C 110 is the peak area of the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode.
[0019] In some embodiments, the negative electrode current collector comprises copper foil, and the thickness D is 4 μm-20 μm.
[0020] In some embodiments, the tensile strength of the negative electrode current collector is X (MPa) and satisfies: 60≤X / D≤100.
[0021] In some embodiments, at room temperature, the elongation of the negative electrode current collector is δ (%), the value range of δ is 3-10, and satisfies: 4≤L / δ≤20.
[0022] In some embodiments, the porosity of the negative electrode sheet is Z (%), the value range of Z is 20-50, and satisfies: 1≤Z / D≤8.
[0023] In some embodiments, the bonding force F (N / m) between the negative electrode active material layer and the negative electrode current collector satisfies: 10≤F≤30, and the negative electrode resistance ranges from 3 to 30 mΩ.
[0024] In some embodiments, the negative electrode active material of the negative electrode active material layer includes at least one of natural graphite, artificial graphite, hard carbon, or soft carbon.
[0025] In some embodiments, the negative electrode undercoat layer includes at least one of carbon black, carbon nanotubes, graphite, acetylene black, and graphene.
[0026] In some embodiments, the present application also provides an electronic device, which includes the above-mentioned electrochemical device.
[0027] This application has at least the following beneficial effects:
[0028] The electrochemical device and negative electrode sheet of the present application can effectively control the risk of collector extension caused by volume changes of active materials during the charge and discharge process of the electrochemical device and the breakage of the positive electrode sheet caused by the extension of the negative electrode sheet by adjusting various parameters within the scope of the present application, thereby improving the problems of wrinkling of the negative electrode sheet and deformation of the battery. DETAILED DESCRIPTION
[0029] The exemplary embodiments are described in detail below, but these exemplary embodiments can be implemented in different ways and should not be interpreted as being limited to the embodiments described in this application. On the contrary, the purpose of providing these embodiments is to make the disclosure of this application thorough and complete, and to fully convey the scope of this application to those skilled in the art.
[0030] (Electrochemical Device)
[0031] The electrochemical device may be a capacitor, a lithium ion battery, a sodium ion battery or a zinc ion battery, for example, a lithium ion capacitor, a lithium ion primary battery or a lithium ion secondary battery.
[0032] The electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.
[0033] The present application provides a matching relationship between a negative electrode active material and an undercoat layer and a current collector, by limiting the relationship between the negative electrode active material and the undercoat layer, including the thickness of the undercoat layer, the thickness of the current collector, the thickness of the negative electrode sheet, the compaction density of the negative electrode sheet, and the OI value of the negative electrode sheet. By matching the undercoat layer with a suitable negative electrode active material and the current collector, the risks of current collector wrinkling and rupture caused by the expansion and contraction of the negative electrode active material layer are effectively improved, the risk of battery deformation is reduced, and at the same time, the electrolyte contains sulfur-oxygen double bonds, which further improves the cycle performance and kinetic performance of the electrochemical device.
[0034] [Negative electrode]
[0035] In some embodiments, the negative electrode sheet includes a negative electrode current collector, a negative electrode undercoat layer, and a negative electrode active material layer.
[0036] In some embodiments, the primer layer is disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer is disposed on the primer layer. The primer layer between the current collector and the negative electrode material can closely link the two, which can not only conduct stress and improve adhesion, but also improve the conductivity of the negative electrode material layer and improve its electrochemical performance. In some embodiments, the current collector includes copper foil.
[0037] For convenience, the negative electrode expansion parameters are defined as: J = 100 × (S / L) + P, K = 400 × (D / L) + V OI ; J and K can characterize the XY expansion rate of the negative electrode of the lithium-ion battery.
[0038] In some embodiments, the thickness S (μm) of the negative electrode bottom coating, the thickness L (μm) of the single-sided negative electrode active material layer, and the compaction density P (g / cm 3 ) satisfy the relationship between:
[0039] 3.8≤100×(S / L)+P≤14.
[0040] In some embodiments, the thickness S (μm) of the negative electrode bottom coating, the thickness L (μm) of the single-sided negative electrode active material layer, and the compaction density P (g / cm 3 ) satisfy the relationship between:
[0041] 4.5≤100×(S / L)+P≤7.5.
[0042] Under specific compaction density conditions, if the thickness ratio of the base coating to the active material is too small, the base coating cannot tightly link the current collector and the active material layer, and there is a risk of powder falling off, which affects the conductivity of the battery. When the compaction density is adjusted, the thickness ratio of the base coating to the active material is also adjusted at the same time, so that the negative electrode sheet satisfies 4.5≤100×(S / L)+P≤7.5, the electrochemical device has good low expansion performance and good kinetic performance without reducing energy density or cycle life.
[0043] In some embodiments, the thickness S of the negative electrode bottom coating is 1 μm-5 μm. The bottom coating can improve the bonding force between the active material layer and the current collector, and help release the stress generated when the active material layer expands in the XY direction. If the bottom coating is too thick, the energy density of the battery will be reduced; and when the relative thickness of the bottom coating exceeds a certain value, the charge transfer impedance will increase.
[0044] In some embodiments, the value range of L is 40 μm to 100 μm. The reduction of the thickness of the active material layer will reduce the energy density of the battery; when the thickness of the active material layer increases, the expansion in the XY direction is too large. Because the thickness of the pole piece is too large, the stress release of the active material after full charge is too large, which will directly increase the expansion of the pole piece in the XY direction and the charge transfer impedance, which is not conducive to the dynamic performance of the battery.
[0045] In some embodiments, the ratio of the thickness S (μm) of the negative electrode bottom coating to the thickness L (μm) of the single-sided negative electrode active material layer is 1:8-1:150. If the thickness of the bottom coating is too thick, although it will reduce the expansion in the XY direction, it will also increase the thickness of the pole piece and affect the energy density of the battery; therefore, the above-mentioned matching needs to be met between the bottom coating of the current collector and the active material layer.
[0046] In some embodiments, the OI value V OI The value of OI is 10 to 25. The larger the value of OI is, the more particles are arranged at an angle parallel to the current collector. When the pole piece is fully charged, the expansion in the Z direction increases while the expansion in the XY direction decreases. If the value of OI is too large, the porosity of the pole piece will be too small.
[0047] In some embodiments, the P is from 1.1 g / cc to 1.8 g / cc.
[0048] The compaction density of the negative electrode sheet is too low, resulting in most particles being arranged perpendicular to the current collector. Although this is beneficial to the infiltration of the electrolyte and the reduction of the charge transfer impedance, it will cause the graphite to embed lithium and expand too much in the XY direction after full charge, which is not conducive to the overall deformation of the battery, and will bring about problems such as reduced initial efficiency and electrode sheet delamination.
[0049] Too high a compaction density of the negative electrode sheet will cause most of the particles to be arranged at an angle parallel to the current collector, resulting in poor electrolyte infiltration and a greatly reduced contact area between the material and the electrolyte, which will severely hinder the embedding or extraction of ions and significantly increase the charge transfer impedance, which is not conducive to the kinetic performance of lithium-ion batteries.
[0050] In some embodiments, the thickness D (μm) of the negative electrode current collector satisfies: 50≤400×(D / L)+V OI ≤100; where V OI Indicates the orientation index of the negative electrode active material, according to V OI =C 004 / C 110 Calculate, C 004 is the peak area of the 004 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode, C 110 is the peak area of the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode.
[0051] When the current collector thickness and tensile strength satisfy the above relationship, the negative electrode sheet can significantly reduce the XY expansion rate of the electrode sheet while maintaining the energy density of the battery. This may be because when the current collector thickness and the single-sided thickness of the negative electrode active material layer and the orientation index of the negative electrode active material satisfy the above relationship, the negative electrode current collector can effectively release the XY direction stress generated by the negative electrode active material layer during the cycle, so that the cycle stress of the active material layer is balanced, and the thickness expansion is prevented from being amplified by the uneven XY direction cycle stress; and the current collector thickness has little effect on the internal liquid phase transfer impedance; the current collector thickness is too small to suppress the expansion in the XY direction. In some embodiments, preferably 55≤400×(D / L)+V OI ≤80.
[0052] In some embodiments, the negative electrode current collector comprises copper foil, and the thickness D is 4 μm-20 μm. In some embodiments, the tensile strength of the negative electrode current collector is X (MPa), and satisfies: 60≤X / D≤100.
[0053] In some embodiments, at room temperature, the elongation of the negative electrode current collector is δ (%), the value range of δ is 3-10, and satisfies: 4≤L / δ≤20.
[0054] In some embodiments, the porosity of the negative electrode is Z (%), the value range of Z is 20-50, and satisfies: 1≤Z / D≤8.
[0055] In some embodiments, the bonding force F (N / m) between the negative electrode active material layer and the negative electrode current collector satisfies: 10≤F≤30, and the negative electrode resistance ranges from 3 to 30 mΩ.
[0056] In some embodiments, the negative electrode active material of the negative electrode active material layer includes at least one of natural graphite, artificial graphite, hard carbon, or soft carbon.
[0057] In some embodiments, the negative electrode undercoat layer includes at least one of carbon black, carbon nanotubes, graphite, acetylene black, and graphene.
[0058] [Electrolyte]
[0059] In some embodiments, the electrochemical device further comprises an electrolyte.
[0060] In some embodiments, the electrolyte includes a sulfur-oxygen double bond-containing compound.
[0061] In some embodiments, based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is M (%) and the specific surface area of the negative electrode active material is A (m 2 / g) satisfies: 0.3≤M / A≤3.
[0062] The content of sulfur-oxygen double bond compounds is related to the specific surface area of the negative electrode active material. When 0.3≤M / A≤3, the electrode can expand in the XY direction with good dynamic performance. If the content of sulfur-oxygen double bond compounds is too low, the SEI formed at the negative electrode is incomplete, resulting in slight lithium deposition and high charge transfer impedance; while if the content of sulfur-oxygen double bond compounds is too high, it will cause slight lithium deposition and excessive charge transfer impedance.
[0063] [Positive electrode]
[0064] The positive electrode sheet includes a positive electrode current collector and a positive electrode membrane.
[0065] The positive electrode current collector is a metal, such as but not limited to aluminum foil.
[0066] The positive electrode membrane is arranged on the surface of the positive electrode current collector. The positive electrode membrane contains a positive electrode active material. When the electrochemical device is a lithium ion battery: the positive electrode active material can be selected from lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, olivine structure lithium phosphate, etc., such as lithium cobalt oxide or lithium manganese oxide, but the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for lithium ion batteries can also be used.
[0067] In some embodiments, the positive electrode active material layer further comprises a positive electrode binder and a positive electrode conductor. The positive electrode binder is used to improve the bonding performance between the positive electrode active material particles and between the positive electrode active material particles and the current collector. In some embodiments, the positive electrode binder includes polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon at least one. In some embodiments, acetylene black is included.
[0068] In some embodiments, the method for preparing the positive electrode sheet is a method for preparing a positive electrode sheet that can be used for an electrochemical device that is well known in the art. In some embodiments, in the preparation of the positive electrode slurry, a solvent is usually added, and the positive electrode active material is added with a binder and a conductive material and a thickener as needed, and then dissolved or dispersed in the solvent to form a positive electrode slurry. The solvent evaporates and is removed during the drying process. The solvent is a solvent that is well known in the art and can be used as a positive electrode active material layer, and the solvent is, for example, but not limited to, N-methylpyrrolidone (NMP).
[0069] [Isolation film]
[0070] In some embodiments, the isolation film is polyethylene, polypropylene, polyvinylidene fluoride or a multilayer composite film thereof.
[0071] In some embodiments, the isolation film is a single-layer isolation film or a multi-layer isolation film.
[0072] In some embodiments, the isolation film is coated with a coating. In some embodiments, the coating comprises at least one of an organic coating and an inorganic coating, wherein the organic coating is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyimide, acrylonitrile-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, acrylic acid-styrene copolymer, polydimethylsiloxane, sodium polyacrylate, and sodium carboxymethyl cellulose, and the inorganic coating is selected from at least one of SiO2, Al2O3, CaO, TiO2, ZnO, MgO, ZrO2, and SnO2.
[0073] The present application has no particular limitation on the shape and thickness of the separator. The method for preparing the separator is a method for preparing a separator that can be used in an electrochemical device and is well known in the art.
[0074] [case]
[0075] In some embodiments, the positive electrode sheet, the isolation membrane and the negative electrode sheet are stacked in order so that the isolation membrane is between the positive electrode sheet and the negative electrode sheet, and then a wound battery (or electrode assembly) is obtained by winding. The battery is placed in a shell, and the electrolyte is injected. After vacuum packaging, standing, formation, vacuum forming and other processes, an electrochemical device can be obtained.
[0076] In other embodiments, the electrochemical device is used in conjunction with a circuit protection board.
[0077] The housing is a hard shell housing or a flexible shell. The material of the hard shell is, for example, metal. The flexible shell is, for example, a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0078] (Electronic Devices)
[0079] The present application also provides an electronic device including the above-mentioned electrochemical device. The electronic device of the present application is any electronic device, such as but not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor. It is noted that the electrochemical device of the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic devices listed above. Air vehicles include air vehicles within the atmosphere and air vehicles outside the atmosphere.
[0080] [test]
[0081] Some specific examples and comparative examples are listed below to better illustrate the present application. In the following examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0082] The lithium-ion batteries of the present application are prepared according to the following method:
[0083] (1) Preparation of positive electrode sheet
[0084] The positive electrode active material lithium cobalt oxide (molecular formula LiCoO2), the conductive agent acetylene black, and the binder polyvinylidene fluoride (abbreviated as PVDF) are mixed in a weight ratio of 96:2:2, and then fully stirred and mixed in an appropriate amount of N-methylpyrrolidone (abbreviated as NMP) solvent to form a uniform positive electrode slurry; the slurry is coated on the current collector Al foil, dried, cold pressed, and cut into strips to obtain positive electrode sheets.
[0085] (2) Preparation of negative electrode
[0086] The current collector is made of copper foil, and the negative electrode active material graphite, thickener sodium carboxymethyl cellulose (abbreviated as CMC), and binder styrene butadiene rubber (abbreviated as SBR) are mixed in a weight ratio of 95:2:3, and then fully stirred and mixed in an appropriate amount of deionized water solvent to form a uniform negative electrode slurry; the slurry is coated on the above copper foil pre-coated with a primer layer (the default copper foil thickness is 6μm, the tensile strength is 450MPa, and the elongation is 4%), and the negative electrode sheet is obtained after drying, cold pressing, and stripping. Among them, the conductive carbon material of the primer layer is selected from at least one of carbon black, carbon nanotubes, graphite, acetylene black, and graphene.
[0087] (3) Preparation of isolation membrane
[0088] 7um PE porous polymer film is used as the isolation membrane
[0089] (4) Preparation of electrolyte
[0090] In a dry argon environment, EC, DMC and DEC are mixed in a weight ratio of 1:1:1, and LiPF6 is added and mixed evenly to form a basic electrolyte, wherein the content of LiPF6 is 12.5%. Sulfur-oxygen double bond compounds are added to the basic electrolyte according to percentage.
[0091] (5) Preparation of lithium-ion batteries
[0092] The positive electrode sheet, negative electrode sheet and separator are taken and wound to form an electrode assembly, and then the electrode assembly is welded to the terminal, packaged with aluminum foil, injected with liquid, left to stand, formed, and vacuumed to form a lithium-ion battery.
[0093] A lithium-ion battery prepared according to the above method is tested for battery performance. In the embodiments, the types and contents of the substances or additives used, and the performance test results of the lithium-ion battery are shown in Tables 1 to 4, wherein the content of each additive is the weight percentage calculated based on the mass of the electrolyte. Unless otherwise specified, the DCR described in this application refers to the DC resistance of a lithium-ion battery at 10% state of charge (SOC).
[0094] Next, the performance of the lithium-ion battery was tested.
[0095] [Measurement of negative electrode sheet parameters]
[0096] (1) Pole OI value V OI :
[0097] The tested battery was disassembled to obtain the negative electrode sheet, which was then immersed in ethyl methyl carbonate (EMC) for cleaning. The XRD was tested using a Bruker X-ray diffractometer in accordance with the general rules for X-ray diffraction analysis and the method for determining lattice parameters of artificial graphite JIS K 0131-1996 and JB / T 4220-2011. The different peak position changes represent the different sizes of graphite unit cells, which can reflect the graphitization process of the graphite material. The peak area is obtained by integrating the peak intensity and the half-peak width. Among them, VOI represents the orientation index of the negative electrode active material, which is calculated according to V OI =C 004 / C 110 Calculation is performed, C004 is the peak area of the 004 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode, C 110 is the peak area of the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode.
[0098] (2) Pole compaction density P:
[0099] The battery under test was placed at 25°C for 5 minutes, and the lithium-ion battery was charged to 3.85V (i.e. 50% SOC) at a constant current of 0.7C. The battery was then disassembled in a drying room. After the electrolyte evaporated, the mass of the negative electrode per unit area (g / cm 2 ) and the thickness of the negative electrode sheet (cm) (the number of collection points is greater than 14). The compaction density of the negative electrode sheet PD = the mass of the negative electrode sheet per unit area (g / cm 2 ) / negative electrode sheet thickness (cm).
[0100] (3) Pole piece adhesion test
[0101] Disassemble the tested battery to obtain the negative electrode sheet coated with negative electrode material on both sides, and immerse the negative electrode sheet in ethyl methyl carbonate (EMC) for cleaning. Take a 15-20cm electrode sheet coated with negative electrode material on both sides; stick the electrode sheet on a steel plate with 3M double-sided tape; use a material testing machine INSTRON 3365 to test the electrode sheet to obtain the relationship between force and distance; and calculate the electrode sheet bonding force value.
[0102] (4) Negative electrode current collector tensile strength test
[0103] The negative electrode sheet was obtained by disassembling the tested battery, and the negative electrode current collector was obtained after removing the negative electrode active material and the bottom coating. At a test temperature of 25°C, the negative electrode current collector was cut into a length × width of 200mm × 15mm, and the tensile properties were tested using a universal material testing machine 5848 at a tensile rate of 50mm / min. The tensile strength and elongation were calculated from the maximum load and length elongation when the sample was broken.
[0104] (5) Negative electrode sheet porosity test
[0105] The negative electrode sheet was obtained by disassembling the tested battery and then immersed in ethyl methyl carbonate (EMC) for cleaning. The density was measured by gas displacement method using an American McMurraytick true density meter (ACCUPYC II1345). The percentage of the pore volume in the electrode sheet to the total volume of the electrode sheet is the electrode sheet porosity, calculated by the following formula: porosity = (V-V0) / V×100%, where V0 is the true volume and V is the apparent volume.
[0106] (6) Negative electrode resistance test:
[0107] Disassemble the battery under test to obtain the negative electrode sheet, and immerse the negative electrode sheet in ethyl methyl carbonate (EMC) for cleaning. The four-probe method is used to measure the resistivity of the electrode sheet. The instrument used for the four-probe method test is a precision DC voltage and current source (SB118 model). Four copper plates with a length of 1.5cm, a width of 1cm, and a thickness of 2mm are fixed equidistantly in a line. The spacing between the two middle copper plates is L (1cm to 2cm), and the base material for fixing the copper plates is an insulating material. During the test, the lower end faces of the four copper plates are pressed on the electrode sheet to be tested, and the DC current I is connected to the copper plates at both ends. The voltage V is measured at the two middle copper plates, and the I and V values are read three times. The average value of I and V is taken, and V / I is the electrode sheet resistance at the test point.
[0108] [Battery electrochemical performance test]
[0109] (1) Negative electrode expansion test along X / Y direction
[0110] The battery under test was placed at a test temperature of 25°C, left to stand for 5 minutes, and the lithium-ion battery was charged to 4.4V at a constant current of 0.7C, and then charged to 0.05C at a constant voltage of 4.4V; the battery was disassembled in a drying room, and part of the negative electrode sheet was cut off. The width of the negative electrode sheet along the X / Y direction was tested by CCD, and compared with the width of the electrode sheet collected after cold pressing, the expansion rate of the electrode sheet along the X / Y axis direction was obtained.
[0111] (2) Dynamic performance test
[0112] Take the battery under test at a test temperature of 25℃, let it stand for 5 minutes, charge the lithium-ion battery to 4.4V with a constant current of 2C, and then charge it to 0.05C with a constant voltage of 4.4V; let it stand for 5 minutes, and then discharge it to 3V with a constant current of 0.5C, and let it stand for 5 minutes. After repeating the above charging and discharging process 10 times, fully charge the battery, disassemble it in a drying room, and observe the lithium deposition on the surface of the negative electrode. Count the area of the gray and golden parts of the surface of the negative electrode, of which the gray part is the area of the lithium deposition part.
[0113] Lithium deposition area percentage = lithium deposition area / total negative electrode area * 100%
[0114] The larger the lithium deposition area, the worse the kinetics and charging capacity, and the smaller the lithium deposition area, the better the kinetics and charging capacity.
[0115] (3) Electrochemical impedance spectroscopy (EIS)
[0116] a) Preparation and lithium plating of a three-electrode battery. The preparation method of the lithium-ion battery is consistent with that of the above-mentioned lithium-ion battery. During the preparation of the lithium-ion battery, a copper wire is connected to the battery as a reference electrode. The contact position of the copper wire is a blank area of the negative electrode current collector without an active material layer, and is close to the position of the pole ear, but not in contact with the pole ear. Then, lithium is plated at the contact area between the copper wire and the negative electrode current collector for 6 hours at a current of 20 μA. After the lithium plating is completed, EIS is tested.
[0117] b) EIS test steps: The lithium-plated three-electrode battery was connected to the Bio-Logic VMP3B electrochemical workstation produced by Bio-LogiC for testing. The test frequency range was 30mHz to 50kHz and the amplitude was 5mV. After the data was collected, the impedance complex plane diagram was used to analyze the data to obtain the Rct data.
[0118] (4) Lithium ion liquid phase transfer impedance (Rion)
[0119] The lithium-ion battery was connected to the Bio-Logic VMP3B electrochemical workstation produced by Bio-LogiC for testing, with a frequency range of 30mHz to 50kHz and an amplitude of 5mV. After data collection, the impedance complex plane diagram was used to analyze the data and obtain the lithium ion liquid phase transfer impedance (Rion).
[0120] (5) DC resistance test (DCR)
[0121] At 0℃, charge the lithium-ion battery to 4.45V at 1.5C constant current, then charge to 0.05C at constant voltage; let stand for 30 minutes; discharge at 0.1C for 10 seconds (take a point every 0.1 seconds and record the corresponding voltage value U1), and discharge at 1C for 360 seconds (take a point every 0.1 seconds and record the corresponding voltage value U2). Repeat the charge and discharge steps 5 times. "1C" is the current value that completely discharges the battery capacity within 1 hour. Calculate DCR according to the following formula: R = (U2-U1) / (1C-0.1C).
[0122] Table 1 lists the relationship between the electrode expansion parameter J, the electrode XY expansion rate and the charge transfer impedance Rct of different negative electrode sheets used in Examples 1 to 7 and Comparative Examples 1 to 5 at different primer thicknesses, electrode thicknesses and electrode compaction densities.
[0123] Table 1 Parameters of Examples 1-7 and Comparative Examples 1-5
[0124]
[0125] Comparing Examples 1-7 and Comparative Examples 1-3 in Table 1, it can be seen that the XY expansion ratio of Examples 1-5 is less than that of Comparative Example 1, and the charge transfer impedance is also less than that of Comparative Example 1. In each embodiment, the pole piece expansion parameter J satisfies 3.8≤J≤14. At this time, the bottom coating layer can improve the bonding force between the active material layer and the current collector, which helps to release the stress generated when the active material layer expands in the XY direction; and the conductive agent on the bottom coating layer helps to improve the conductivity of the lithium-ion battery, which is reflected in the reduction of charge transfer impedance. However, the ratio of the bottom coating thickness to the negative electrode active material layer thickness of Comparative Example 1 is low, so that under similar compaction density conditions, the bottom coating layer cannot form an effective slow release effect on the cyclic stress, which is not conducive to the expansion in the XY direction and the battery dynamics performance.
[0126] The compaction density of the electrode used in Comparative Example 3 is relatively low, which is conducive to the infiltration of the electrolyte and the reduction of Rct, but to a certain extent, it will cause the graphite to embed lithium after full charging and increase the expansion in the XY direction, which may bring about problems such as reduced initial efficiency and electrode demolding.
[0127] The compaction density of the pole piece used in Comparative Example 4 is too large. Although the pole piece expansion parameter J>3.8 and the pole piece expansion in the XY direction is ≤0.5%, the high compaction density will cause most of the particles to be arranged at an angle parallel to the current collector, resulting in poor electrolyte infiltration and a greatly reduced contact area between the material and the electrolyte, which leads to severe obstruction of ion embedding or extraction and a significant increase in Rct, which is not conducive to the kinetic performance of lithium-ion batteries.
[0128] The ratio of the primer thickness to the electrode thickness used in Comparative Example 5 is too high, resulting in a electrode expansion parameter J>14. Although the electrode expands less in the XY direction, there is no benefit in terms of energy density.
[0129] On the whole, when 4.5≤J≤7.5, the battery can maintain a high energy density and dynamic performance while significantly reducing the XY expansion rate of the negative electrode sheet. At this time, the XY expansion of the negative electrode sheet when fully charged is ≤0.5%.
[0130] Table 2 lists the effects of the physical parameters of the current collector copper foil and the electrode OI value on the electrode XY expansion rate and liquid phase transfer impedance of the negative electrode sheets of Examples 8-12 and Comparative Examples 6-9 when the base coating thickness is 1.5 μm and the compaction density is 1.50 g / cc.
[0131] Table 2 Parameters of Examples 8-12 and Comparative Examples 6-9
[0132]
[0133] From the comparison of Examples 8-12 and Comparative Examples 7-8 in Table 2, it can be seen that when the expansion parameter K ≥ 50, the pole piece expands in the XY direction ≤ 0.4%. This may be because when the thickness of the current collector satisfies the single-sided thickness of the negative electrode active material layer and the orientation index of the negative electrode active material, the negative electrode current collector can effectively release the XY direction stress generated by the negative electrode active material layer during the cycle, so that the cyclic stress of the active material layer is balanced, avoiding the thickness expansion from being amplified by the uneven XY direction cyclic stress, and the release in the Z direction after the pole piece is fully charged can also improve the expansion in the XY direction.
[0134] In Comparative Example 6, when the pole piece OI value is ≥25, the material has poor wettability with the electrolyte, and the liquid phase transfer impedance increases significantly. The pole piece OI value used in Comparative Example 7 is too small, and the particle arrangement tends to be perpendicular to the current collector direction, resulting in excessive expansion in the XY direction after full charge. Therefore, the pole piece OI value of 15 to 25 can ensure small expansion in the XY direction while taking into account a small liquid phase transfer impedance.
[0135] The copper foil thickness used in Comparative Example 9 is too large, and K>100. Although the expansion in the XY direction is small, the impact on the battery energy density is very large. Therefore, the copper foil thickness is 6-10 μm, and 50≤K≤100 is satisfied, which can ensure that excellent XY expansion performance is obtained without losing too much energy density.
[0136] Table 3 lists the effects of the thickness of the primer layer and the content of the S=O double bond compound in the electrolyte on the kinetic performance when the copper foil thickness is 6 μm, the electrode thickness is 65 μm, and the electrode compaction density is 1.50 g / cc.
[0137] Table 3 Parameters of Examples 13-17 and Comparative Examples 10-11
[0138]
[0139] It can be seen from Examples 14 and 17 and Comparative Examples 10-11 that when the content of the S=O compound is controlled at 0.5-1%, the SEI film thickness and impedance on the negative electrode surface can be reduced, and the kinetic performance can be improved; when the content of the S=O compound is 2-3%, the DCR impedance will increase accordingly.
[0140] The content of the S=O compound is related to the specific surface area of the negative electrode active material. When 0.3≤M / A≤3, the expansion of the electrode in the XY direction can be within the range of weight 1 and have good dynamic performance.
[0141] In Comparative Example 10, the M / A ratio is too low, and the SEI formed by the electrolyte at the negative electrode is incomplete, resulting in slight lithium deposition and higher DCR impedance; while in Comparative Example 11, the content of S=O compounds is too high, resulting in more serious lithium deposition and excessive DCR impedance.
[0142] Table 4 lists the effects of different negative electrode sheets with different primer thicknesses on the negative electrode sheet adhesion and negative electrode sheet resistance.
[0143] Table 4 Parameters of Examples 19-23 and Comparative Example 12
[0144]
[0145] In Examples 19-23 and Comparative Example 12, when the thickness of the primer layer is 1.5-3 μm, increasing the thickness of the primer layer is beneficial to the bonding effect between the negative electrode active material and the current collector, and the negative electrode sheet resistance is low; when the thickness of the primer layer is further increased, the electrode sheet resistance increases significantly, so the thickness of the primer layer should not be too large. The thickness of the primer layer used in Comparative Example 12 is too small, which makes the electrode sheet bonding force too small, and the negative electrode sheet resistance increases significantly, which is not conducive to the battery dynamics performance.
[0146] The above disclosed features are not intended to limit the scope of implementation of the present disclosure. Therefore, all equivalent changes made to the contents described in the claims of the present disclosure should be included in the scope of the claims of the present disclosure.
Claims
1. An electrochemical device comprising a negative electrode sheet, wherein: The negative electrode sheet comprises a negative electrode current collector, a negative electrode bottom coating layer and a negative electrode active material layer; The primer layer is disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer is disposed on the primer layer; The thickness of the negative electrode primer layer is S μm, the thickness of the single-sided negative electrode active material layer is L μm, and the compaction density of the negative electrode active material layer is P g / cm 3 The relationship between them satisfies: 3.8≤100×(S / L)+P≤14; The thickness S of the negative electrode bottom coating is 1 μm-5 μm; The OI value V of the negative electrode active material layer OI 15 to 25; The value range of L is 40 μm to 100 μm; The P is 1.1 g / cc to 1.8 g / cc; The thickness D μm of the negative electrode current collector, the thickness L of the single-sided negative electrode active material layer, and the orientation index V of the negative electrode active material OI Between: 50≤400×(D / L) + V OI ≤100; in, V OI Indicates the orientation index of the negative electrode active material, according to V OI =C 004 / C 110 Calculate, C 004 is the peak area of the 004 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode, C 110 is the peak area of the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode; The negative electrode current collector comprises copper foil, and the thickness D is 4 μm-20 μm; The tensile strength of the negative electrode current collector is X MPa and satisfies: 60≤X / D≤100; At room temperature, the elongation of the negative electrode current collector is δ%, the value range of δ is 3-10, and satisfies: 4≤L / δ≤20; The porosity of the negative electrode sheet is Z%, the value range of Z is 20-50, and satisfies: 1≤Z / D≤8.
2. The electrochemical device according to claim 1, wherein: The thickness of the negative electrode primer layer is S μm, the thickness of the single-sided negative electrode active material layer is L μm, and the compaction density of the negative electrode active material layer is P g / cm 3 The relationship between them satisfies: 4.5≤100×(S / L) + P≤7.
5.
3. The electrochemical device according to claim 1, wherein The ratio of the thickness S μm of the negative electrode undercoat layer to the thickness L μm of the single-sided negative electrode active material layer is 1:8-1:
150.
4. The electrochemical device according to claim 1, wherein The electrochemical device also includes an electrolyte; The electrolyte includes a sulfur-oxygen double bond-containing compound; Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is M % and the specific surface area of the negative electrode active material is A m 2 / g satisfies: 0.3≤M / A≤3.
5. The electrochemical device according to claim 4, wherein: The sulfur-oxygen double bond compound is selected from at least one of methylene disulfonate, vinyl sulfate, propylene sulfate, 1,3-propane sultone, 1,4-butane sultone, ethylene sultone, 1,3-propene sultone, 1,4-butene sultone, 1-methyl-1,3-propene sultone, divinyl sulfone, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone and methyl vinyl sulfone.
6. The electrochemical device according to claim 1, wherein The bonding force FN / m between the negative electrode active material layer and the negative electrode current collector satisfies: 10≤F≤30, and the negative electrode resistance has a value range of 3-30 mΩ.
7. The electrochemical device according to claim 1, wherein: The negative electrode active material of the negative electrode active material layer includes at least one of natural graphite, artificial graphite, hard carbon or soft carbon; The negative electrode bottom coating layer includes at least one of carbon black, carbon nanotubes, graphite, and graphene.
8. An electronic device comprising the electrochemical device according to any one of claims 1 to 7.
Citation Information
Patent Citations
Negative electrode material and electrochemical device using the same
CN109873144A
Electrochemical device and electronic device
CN113161515A
Electrochemical device and electronic device
CN113948675A